Ph Responsive In-Vitro Drug Release Behavior of Poly (Malic Acid-Co-Butane-1,4-Diol-Co-Maleic Acid) - Mahmud, Abu; Bakr, Abu (European Journal of Applied Sciences, 2021)
Four mixtures of malic acid and maleic acid in mole combinations (1.0+0.1), (1.0+0.2), (1.0+0.3), and (1.0+0.4) respectively were separately polymerized with one mole of butane 1,4-diol in Dean-Stark apparatus using xylene as the reaction medium. Among the synthesized co-polyesters, sample II had the highest molecular weight and it was selected for subsequent experiments. It was characterized by its IR-spectrum, solubility in common organic solvents, elemental analysis and hydrolytic degradation test. It was found from hydrolytic degradation test that the said polyester sample did not degrade or swell in acid medium but gradually degraded in basic medium. Because of having such pH responsive behavior it was tried as an enteric coating material on diclofenac sodium core tablets. In vitro drug release pattern of co-polyester coated samples matches with the British Pharmacopoeia standard drug release profile of enteric-coating material.